The analyse of the automotive alternator as a generator in Picohydro system: Laboratory experiment test. (February 2020) - Adibowo, S; Uyun, A S; Nur, S M; Abdullah, K; Yandri, E; Adiatmojo, G D
Abstract: The aim of this article is to evaluate the feasibility of using an automotive alternator as a Pico water turbine (Picohydro). The automotive alternator system is examined by the pump as a turbine, using water energy in the simulator system to generates the automotive alternator. The simulator equipment that has been made is used to see the performance of the automotive alternator as a generator and recorded a few parameters in the closed-loop system. From this evaluation, the greater the water flow or water pressure that drives the pump as a turbine, the higher the power is produced from the automotive alternator. The Study shows that automotive alternator can be used as a generator and an alternative to generating electricity.